Governance Indicators and Foreign Direct Investment in Nigeria (1996-2017) (Economics and region, 2019)
This study examines the impact of governance indicators on Foreign Direct Investment (FDI) in Nigeria between 1996 and 2017 using ANOVA method. The Bartlett's Chi-square test for equal variances is used to check the reliability of the result. The results indicate that net inflow of FDI is sensitive to index of political stability, violence and terrorism; index of control of corruption; index of regulatory quality; and index of rule of law but not sensitive to index of government effectiveness and index of voice and accountability. The study recommends that government agencies responsible for promoting FDI inflow into Nigeria should be more transparent in their dealings so as to improve all the important governance indexes.
Keywords: foreign direct investment; corruption index; regulatory quality; rule of law; political stability; violence and terrorism